Application of birnessite type manganese oxide catalyst in preparation of lignin polyol
By using a water-sodium manganese ore-type manganese oxide catalyst doped with Na and Cu, the problems of complex and long time in the prior art lignin hydrothermal degradation process are solved, and the quality of lignin polyols and the reduction of catalyst usage are achieved.
Patent Information
- Application Number
- CN202411744874.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
AI Technical Summary
In the prior art, when using manganese dioxide catalyst for hydrothermal degradation of lignin, the degradation product needs to be precipitated with dilute acid before hydroxylation modification, which is complicated and time is long.
The catalyst is prepared by using sodium-manganese ore-type manganese oxide catalyst doped with Na and Cu, by heating and cooling treatment, and used during the liquefaction of lignin.
The catalyst preparation process is simplified, the hydroxyl value, acid value and residue ratio of lignin polyol are improved, the quality of polyol is improved, and the catalyst is used in small amounts, which can more effectively change the hydroxyl ratio.
Smart Images

Figure CN119565631A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lignin modification, and in particular to application of a birnessite-type manganese oxide catalyst in the preparation of lignin polyols. Background Art
[0002] Lignin is a material that forms important structures in the supporting tissues of vascular plants and some algae. Lignin has a complex composition, mainly composed of three units: p-guaiacyl, syringyl and p-hydroxyphenyl. The structure of natural lignin is difficult to accurately determine. Liquefaction is a thermochemical process that converts biomass raw materials from solid to liquid mixtures. Liquefaction can degrade polyhydroxy polymers in lignin into liquid polyol mixtures. These hydroxyl-containing polyols can replace petroleum-based polyethers or polyester polyols to prepare polyurethanes.
[0003] In order to improve the efficiency of the liquefaction reaction, a catalyst needs to be added thereto, and manganese-containing catalysts are often used in the reaction. The patent "CN 112778540 B A lignin-based polyol for synthesizing polyurethane and its preparation method" mentions the use of manganese dioxide as a catalyst, but the addition of manganese dioxide catalyzes the hydrothermal degradation of lignin, and the degradation product needs to be precipitated with dilute acid and then hydroxylated. The process of preparing lignin polyols is complicated and time-consuming. Birnessite is the most common type of manganese mineral in soil and sediments. The manganese in it is usually mainly +4 and +3 valence manganese. It is a layered manganese mineral formed by a layer of MnO6 octahedrons and a layer of water molecules stacked alternately, and has unique surface electrochemical properties, cation exchangeability and redox properties. Birnessite is mostly a hexagonal symmetrical structure with varying numbers of octahedral vacancies in the structure. These vacancies are strong adsorption sites for heavy metals. The article "Adsorption of several heavy metal ions by birnessite and its relationship with manganese oxidation degree and adsorption sites" believes that birnessite can adsorb different metal ions. Doping birnessite with different metals may change the original properties of birnessite, but the role of birnessite as a catalyst in the liquefaction of lignin after adsorbing these different metal ions remains unknown. Summary of the invention
[0004] In view of the above prior art, the object of the present invention is to provide an application of a birnessite-type manganese oxide catalyst in the preparation of lignin polyols.
[0005] To achieve the above object, the present invention adopts the following technical solution:
[0006] In a first aspect of the present invention, a metal-doped birnessite-type manganese oxide catalyst is provided, wherein the doped metal in the birnessite-type manganese oxide catalyst is one or more of Na and Cu.
[0007] Furthermore, the molar ratio of manganese element to doping metal is 1:(0.05-10).
[0008] Furthermore, the birnessite-type manganese oxide catalyst is prepared by the following method:
[0009] The nitrate and potassium permanganate are mixed, heated in air, cooled, washed, filtered, solid matter is collected, and dried to obtain a birnessite-type manganese oxide catalyst;
[0010] The nitrate is one or more of sodium nitrate and copper nitrate.
[0011] Furthermore, during the heating process, the temperature is raised from room temperature to 900-1100° C. over 1-5 hours, and the constant temperature of 900-1100° C. is maintained for 4-6 hours.
[0012] The second aspect of the present invention provides the use of the metal-doped birnessite-type manganese oxide catalyst in lignin liquefaction.
[0013] A third aspect of the present invention provides a method for liquefying lignin, comprising the following steps:
[0014] After polyethylene glycol 400, glycerol and sulfuric acid are mixed, the metal-doped birnessite-type manganese oxide catalyst is added, and lignin is added. The mixture is heated to reflux under nitrogen protection and stirred continuously to obtain lignin polyol.
[0015] Furthermore, the mass ratio of polyethylene glycol 400, glycerol, sulfuric acid, lignin and metal-doped birnessite-type manganese oxide catalyst is (100-500) g: (20-100) g: (1-10) g: (20-100) g: (0.01-1) g.
[0016] The fourth aspect of the present invention provides a lignin polyol, wherein the lignin polyol is prepared by the method described above.
[0017] The fifth aspect of the present invention provides the use of the lignin polyol in the preparation of controlled-release fertilizer coating materials.
[0018] The sixth aspect of the present invention provides a controlled-release fertilizer coating material, comprising the lignin polyol described above, wherein the mass ratio of lignin polyol to PAPI in the lignin polyol controlled-release fertilizer coating material is (0.01-5):1.
[0019] Beneficial effects of the present invention:
[0020] 1. The present invention uses sodium nitrate, copper nitrate and potassium permanganate as raw materials to prepare a Na- and Cu-doped birnessite-type manganese oxide catalyst N1C1. The catalyst preparation process provided in the present invention is simple and the finished product has stable properties.
[0021] 2. The prepared catalyst is used for liquefaction of lignin to obtain lignin polyol. The catalyst is used in small amounts and can change the hydroxyl ratio. The hydroxyl value, acid value and residue rate of the lignin polyol are all improved, thereby improving the quality of the polyol.
[0022] 3. The lignin polyol prepared by the present invention has a higher hydroxyl value, a lower impurity content, and a more complete reaction with isocyanate, and can form a polyurethane membrane shell with a dense structure, thereby extending the fertilizer nutrient release cycle. In addition, the biomass material has a stronger degradation ability than petroleum-based polyols and is more environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 XRD patterns of the four catalysts.
[0024] Figure 2 This is an electron microscope scanning image of the membrane shell of the controlled-release fertilizer prepared with CLP1, LP1, LP2, LP3, and LP4 as liquefied materials (the image magnification is 5000×). DETAILED DESCRIPTION
[0025] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0026] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific embodiments.
[0027] The test materials used in the examples of the present invention that are not specifically described are all conventional test materials in the art and can be purchased through commercial channels. The CAS number of the lignin used in the present invention is 8068-03-9, and the sulfuric acid used is concentrated sulfuric acid with a mass fraction of 98%.
[0028] Example 1: Na- and Cu-doped birnessite-type manganese oxide catalyst
[0029] The Na- and Cu-doped birnessite-type manganese oxide catalyst N1C1 is prepared by the following method:
[0030] Sodium nitrate and copper nitrate are mixed in a molar ratio (mol / mol) of 1:1 to obtain metal nitrate powder. Potassium permanganate powder and metal nitrate powder are mixed in a molar ratio (mol / mol) of manganese element in potassium permanganate to metal ion in metal nitrate powder of 10:1, and then heated from room temperature to 1000°C in an air atmosphere for 2 hours, and kept at 1000°C for 5 hours. After cooling, the mixture is washed, filtered, and the solid matter is collected and dried to obtain the Na- and Cu-doped birnessite-type manganese oxide catalyst N1C1.
[0031] Example 2: Liquefaction of lignin
[0032] 250g of polyethylene glycol 400, 50g of glycerol and 2.5g of sulfuric acid were added to a three-necked flask, the reactor was preheated to 140°C and protected with nitrogen, the reflux condenser was turned on, and the electric stirrer was set to rotate at 800 rpm. Then, 50g of lignin was added to the reactor, mixed with the solution, and refluxed. The electric stirrer was stirred continuously during the reaction. After liquefaction for 1 hour, 0.3g of catalyst was added, and the reaction was continued for 1 hour. After the reaction was completed, the liquefied product was taken out from the reactor and divided into two parts of equal volume. One part of the liquefied product was recorded as CLP, which was the uncentrifuged product; the other part of the liquefied product was centrifuged and stood at a centrifugal speed of 4000rpm for 10 minutes, and then stood at a standing temperature of 25°C for 7 days. After standing, 70% of the total liquid volume was sucked from the upper layer of the liquid with a syringe as the upper solution (CLP1), and the remaining 30% was the lower solution (CLP2).
[0033] The catalyst used in this Example 2 is the Na- and Cu-doped birnessite-type manganese oxide catalyst N1C1 prepared in Example 1.
[0034] Comparative Example 1
[0035] Lignin liquefaction
[0036] The difference from Example 2 is that no catalyst is used in this comparative example. The product before centrifugation is recorded as MIX1; the upper layer solution obtained after the product is centrifuged and allowed to stand is recorded as LP.
[0037] Comparative Example 2
[0038] Catalyst preparation
[0039] The preparation method of the common birnessite-type manganese oxide catalyst NOCO used in this comparative example is different from the preparation method of the catalyst in Example 1 in that no metal nitrate powder is added during the preparation process. The specific preparation method is as follows:
[0040] 4 g of potassium permanganate was ground and spread in a crucible, and calcined at high temperature in a muffle furnace. The temperature was raised from room temperature to 1000° C. in an air atmosphere for 2 hours, and then kept at 1000° C. for 5 hours. After cooling to room temperature, it was washed with deionized water several times, filtered, and the solid matter was collected and dried at 105° C. for 2 hours to obtain a common birnessite-type manganese oxide catalyst NOC0.
[0041] Lignin liquefaction
[0042] The obtained common birnessite-type manganese oxide catalyst NOC0 was used for lignin liquefaction. The lignin liquefaction method of this comparative example is different from that of Example 2 in that the catalyst used in this comparative example is a common birnessite-type manganese oxide catalyst NOC0.
[0043] The uncentrifuged product was recorded as MIX2; the upper layer solution obtained after the product was centrifuged and allowed to stand was recorded as LP2.
[0044] Comparative Example 3
[0045] Catalyst preparation
[0046] The preparation method of the Na-doped birnessite-type manganese oxide catalyst N1C0 used in this comparative example is different from the preparation method of the catalyst in Example 1 in that the metal nitrate powder used in the preparation process is metal sodium nitrate powder. The specific preparation method is as follows:
[0047] Potassium permanganate powder and metal nitrate powder are mixed in a molar ratio (mol / mol) of potassium ions in potassium permanganate to metal ions in metal nitrate powder of 10:1, and then heated from room temperature to 1000°C in an air atmosphere for 2 hours, and kept at 1000°C for 5 hours. After cooling, the mixture is washed, filtered, and the solid matter is collected and dried to obtain a Na-doped birnessite-type manganese oxide catalyst N1C0.
[0048] Lignin liquefaction
[0049] The obtained Na-doped birnessite-type manganese oxide catalyst N1C0 was used for lignin liquefaction. The lignin liquefaction method of this comparative example is different from that of Example 2 in that the catalyst used in this comparative example is the Na-doped birnessite-type manganese oxide catalyst N1C0.
[0050] The uncentrifuged product was recorded as MIX3; the upper layer solution obtained after the product was centrifuged and allowed to stand was recorded as LP3.
[0051] Comparative Example 4
[0052] Catalyst preparation
[0053] The preparation method of the Cu-doped birnessite-type manganese oxide catalyst NOC1 used in this comparative example is different from the preparation method of the catalyst in Example 1 in that the metal nitrate powder used in the preparation process is metal copper nitrate powder. The specific preparation method is as follows:
[0054] Potassium permanganate powder and metal nitrate powder were mixed at a molar ratio (mol / mol) of potassium ions in potassium permanganate to metal ions in metal nitrate powder of 10:1, and then heated from room temperature to 1000°C in an air atmosphere for 2 hours, and kept at 1000°C for 5 hours. After cooling, the mixture was washed, filtered, and the solid matter was collected and dried to obtain a Cu-doped birnessite-type manganese oxide catalyst NOC1.
[0055] Lignin liquefaction
[0056] The obtained Cu-doped birnessite-type manganese oxide catalyst NOC1 was used for lignin liquefaction. The lignin liquefaction method is different from that of Example 2 in that the catalyst used in this comparative example is the Cu-doped birnessite-type manganese oxide catalyst NOC1.
[0057] The product before centrifugation was recorded as MIX4; the upper layer solution obtained after the product was centrifuged and allowed to stand was recorded as LP4.
[0058] Test Example 1:
[0059] Catalysts N1C1, NOC0, N1C0 and NOC1 prepared in Example 1 and Comparative Examples 2 to 4 were taken and XRD detection was performed on the above catalysts.
[0060] Results Figure 1 The 2θ angles corresponding to the three strong peaks in the XRD spectrum of the synthesized birnessite are 12.3°, 24.8°, and 37.6°, and the corresponding crystal planes are (001), (002), and (012), respectively, which are consistent with the standard card number of manganese dioxide PDF#86-0666, indicating that the synthesized birnessite is hexagonal birnessite.
[0061] Test Example 2:
[0062] Take the uncentrifuged products CLP, MIX1-MIX4 prepared in Example 2 and Comparative Examples 1-4, and dilute them with a mixture of water and 1,4-dioxane solution. The diluted liquid product is separated into residue and filtrate by a high-speed refrigerated centrifuge. After centrifugation, the residue is thoroughly rinsed with deionized water and dried at 105°C to constant weight. The hydroxyl value, acid value and residue rate are measured, wherein the hydroxyl value is measured according to the steps in the national standard "GB / T 12008.3-2009 Plastic polyether polyol Part 3: Determination of hydroxyl value", the acid value is measured according to the steps in the national standard "GB / T 12008.5-2010 Plastic polyether polyol Part 5 Acid value determination", and the residue rate is measured according to the method in "Research on liquefaction of corn stalks by compound liquefaction agent and analysis of products (modern chemical industry)", and the residue rate = residue mass / lignin raw material mass × 100%.
[0063] Table 1 Hydroxyl value, acid value and residue rate data of lignin polyol
[0064]
[0065]
[0066] As can be seen from Table 1, after the catalyst prepared in Example 1 was used in Example 2, the hydroxyl value and acid value of the liquefied product increased significantly, and the residue rate of the product was reduced. Further, liquefaction yield = 100% - residue rate, liquefied product mass = liquefaction yield * mass of lignin added as raw material, since the mass of lignin added as raw material is 50g, therefore, the lower the residue rate, the higher the quality of the liquefied product, and the higher the utilization rate of the raw material. At the same time, the mass of the polyol can be expressed by the hydroxyl value: the mass of the polyol = hydroxyl value * mass of the liquefied product / (56.1 * 1000), therefore, the amount of polyol contained in CLP is the highest.
[0067] All indicators are better than those of product MIX1 without using a catalyst, product MIX2 using a common catalyst, and products MIX3 and MIX4 using a single nitrate.
[0068] Test Example 3:
[0069] Preparation of coated controlled release fertilizer
[0070] Using model fertilizer urea granules as fertilizer cores, and using CLP1, LP1-LP 4 prepared in Example 2 and Comparative Examples 1-4 as liquefied materials, the experiment was divided into 5 groups, each group using 1 kg of fertilizer cores, to prepare lignin polyol-based coated fertilizers under laboratory conditions.
[0071] First, put the fertilizer core into the barrel and preheat it at 75°C for 20 minutes. After the preheating stage, 5g of polyolefin wax particles are distributed on the surface of the urea pellets and the reaction is continued for 7 minutes. The liquefied material is evenly mixed with PAPI at a mass ratio of 0.58:1 (g / g) to obtain a coating material, which is poured on the surface of the rotating urea particles. The coating material added each time accounts for 1% of the weight of the fertilizer and is added 3 times respectively. The coating material is manually sprayed on the surface of the fertilizer roller at a flow rate of 3g / s, and the spraying structure is streamlined. The reaction in the barrel completes the thermal curing process of the composite coating material, synthesizes the bio-based polyurethane film layer, and adheres it to the surface of the fertilizer to obtain a coated controlled-release fertilizer.
[0072] The nitrogen release rate of the coated controlled-release fertilizers obtained in each group was tested and the surface morphology of the fertilizer film shell was scanned by electron microscope. The results are shown in Table 2 and Figure 2 .
[0073] Table 2 Nitrogen release rate detection
[0074]
[0075] As can be seen from Table 2, the controlled-release fertilizer prepared from the lignin polyol (CLP1) of Example 2 has an initial release rate of 0.82% and a release period of 38 days. The catalyst doped with two elements has a relatively stable release rate and a longer release period, and the controlled-release effect is better. Figure 2 From the microscopic morphology, the controlled-release fertilizer prepared by the lignin polyol (CLP1) of Example 2 has fewer voids in the membrane shell and a smoother surface, indicating that the lignin polyol of Example 2 reacts more completely with the isocyanate (PAPI) and the degree of cross-linking is tighter.
[0076] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A metal-doped birnessite-type manganese oxide catalyst, characterized in that: In the birnessite-type manganese oxide catalyst, the doped metal is one or more of Na and Cu.
2. The metal-doped birnessite-type manganese oxide catalyst according to claim 1, characterized in that: The molar ratio of manganese element to doping metal is 1:(0.05-10).
3. The metal-doped birnessite-type manganese oxide catalyst according to claim 1, characterized in that: The birnessite-type manganese oxide catalyst is prepared by the following method: The nitrate and potassium permanganate are mixed, heated in air, cooled, washed, filtered, solid matter is collected, and dried to obtain a birnessite-type manganese oxide catalyst; The nitrate is one or more of sodium nitrate and copper nitrate.
4. The metal-doped birnessite-type manganese oxide catalyst according to claim 3, characterized in that: During the heating process, the temperature is raised from room temperature to 900-1100°C over 1-5 hours, and maintained at a constant temperature of 900-1100°C for 4-6 hours.
5. Use of the metal-doped birnessite-type manganese oxide catalyst according to any one of claims 1 to 4 in lignin liquefaction.
6. A method for liquefying lignin, characterized in that: The steps include: After polyethylene glycol 400, glycerol and sulfuric acid are mixed, the metal-doped birnessite-type manganese oxide catalyst according to any one of claims 1 to 4 is added, and lignin is added. The mixture is heated to reflux under nitrogen protection and stirred continuously to obtain lignin polyol.
7. The method for liquefying lignin according to claim 6, characterized in that: The mass ratio of polyethylene glycol 400, glycerol, sulfuric acid, lignin and metal-doped birnessite-type manganese oxide catalyst is (100-500) g: (20-100) g: (1-10) g: (20-100) g: (0.01-1) g.
8. A lignin polyol, characterized in that The lignin polyol is prepared by the method described in any one of claims 6-7.
9. Use of the lignin polyol according to claim 8 in preparing a controlled-release fertilizer coating material.
10. A controlled-release fertilizer coating material, characterized in that: The invention comprises the lignin polyol as claimed in claim 8, wherein the mass ratio of the lignin polyol to PAPI in the lignin polyol controlled-release fertilizer coating material is (0.01-5):1.
Citation Information
Patent Citations
A lignin-based polyol for synthesizing polyurethane and its preparation method
CN112778540B